Franklin rides a bike - Bourgeois, Paulette; Clark, Brenda (New York, N.Y. : Scholastic, 1999)
Learning to ride a bike is hard for Franklin. Will he do it?
"This edition is only available for distribution through the school market."--P. [4] of cover.
"RL: 2"--P. [4] of cover.
"004-007"--P. [4] of cover.
Keywords: Bicycles and bicycling -- Fiction; Turtles -- Fiction; Animals -- Fiction